Quality of life related to periodontal disease in diabetic patients under the health subsidized regime in Manizales - Chacón-Arboleda, Paula Tatiana; Joya-Rodríguez, Luz Dary; Cardona-Rivas, Dora (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Introduction: quality of life related to oral health is a relevant topic that involves the relationship of dentistry with chronic noncommunicable diseases such as diabetes, given its bidirectional relationship. This study emphasizes the importance of reviewing the impact of periodontal alterations on the quality of life of diabetic patients. The objective of this study was to establish the quality of life related to periodontal status in diabetic patients belonging to the subsidized regime of Manizales. Methods: 90 diabetic adults belonging to the diabetes program of the subsidized regime were observed by means of a structured interview, application of the OHIP-14 instrument (Oral Health Impact Profile on Quality of Life) and direct observation of periodontal status, to establish the index of periodontal extension and severity, description of the OHIP-14 index, establish its relationship with sociodemographic variables and with periodontal health status. Results: we found a prevalence of impaction according to OHIP-14 of 44.4%, extent of impaction with an average of 1.58 (CI: 1.0-2.1) and severity of impaction of 6.7 (CI: 6.2-7.8). When consolidating the OHIP-14 results by dimension, it was observed that the greatest impact corresponded to the physical pain dimension, with a percentage of 81.1%. The lowest percentage was presented in the dimensions of Social Incapacity and Disability or Handicap with 34.4%. Conclusions: although in the population studied, the presence of periodontal disease had a poor impact on quality of life, this was greater in the dimensions of physical pain and psychological discomfort.